Важливість мобільної оптимізації вебсайтів для покращення користувацького досвіду та підвищення ефективності бізнес-процесів - Лелюк, О. О. (ХНУРЕ, 2025)
Nowadays the use of mobile devices, optimizing websites for mobile plat forms has become crucial. With over 60% of global web traffic coming from smartphones and tablets, non-optimized sites risk losing a significant portion of their audience. Mobile optimization enhances user experience by ensuring fast loading times, easy navigation, and responsive design, which directly impacts user satisfaction and reduces bounce rates. Faster load times, image optimization, and efficient coding contribute to better performance and higher conversion rates. With mobile use on the rise, optimizing for seamless experiences is essential for businesses to stay competitive in the digital landscape.
Keywords: оптимізація вебсайтів; покращення користувацького досвіду